Odpowiedź:
[tex]a)2\frac{5}{7}+1\frac{2}{5}=2\frac{25}{35}+1\frac{14}{35}=3\frac{39}{35}=4\frac{4}{35}\\\\b)5\frac{5}{7}-2\frac{1}{5}=5\frac{25}{35}-2\frac{7}{35}=3\frac{18}{35}\\\\c) 6\frac{2}{9}-4\frac{3}{7}=6\frac{14}{63}-4\frac{27}{63}=5\frac{77}{63}-4\frac{27}{63}=1\frac{50}{63}\\\\d)\frac{11}{14}*\frac{7}{9}=\frac{11}{18}\\\\e)\frac{5}{7}:\frac{10}{21}=\frac{5}{7}*\frac{21}{10}=\frac{21}{14}=1\frac{1}{2}\\\\f)2\frac{3}{5}*7\frac{1}{2}=\frac{13}{5}*\frac{15}{2}=\frac{39}{2}=19\frac{1}{2}[/tex]